Do dividends pattern follow earnings pattern? Evidence from Nigerian financial sector - Abdulkadir, Rihanat Idowu; Abdullah, Nur Adiana Hiau; Wong, Woei Chyuan (IISTE, 2014)
The argument that the relationship between earnings and dividend have weakened stimulates the interest to revisit the relationship. The study adopts two approaches in testing this relationship.Using descriptive analysis, the study follow the approach of recent empirical studies in developed market to test whether dividend concentration exists among financial firms in the Nigerian market and whether this is driven by earnings concentration among the firms. Secondly, the study tests the relationship between earnings and dividend in a regression model to confirm whether this relationship has weakened or not. Findings based on a sample of 49 financial firms on the Nigerian Stock Exchange indicates presence of dividend concentration and show that this is as a result of earnings concentration.Findings from fixed effects regression estimates also indicate that earnings have strong predictive power in explaining dividend payout even when other determinants are accounted for. Based on the combined evidence from descriptive analysis and regression results, the study concludes that dividends are sensitive to earnings and the relationship between the two remain strong in explaining payout policies in the Nigerian financial service sector.